2020
DOI: 10.1111/efp.12620
|View full text |Cite
|
Sign up to set email alerts
|

First record of Ektaphelenchoides pini associated with Ips sexdentatus on Pinus nigra laricio in Italy

Abstract: In February 2015, an unexpected windstorm downed five hectares of a European black pine Pinus nigra subsp. laricio forest formation located close to Vallombrosa, Florence (Central Italy). In the following spring, an extensive survey was conducted in the area. Felled trees, stumps and all the suitable plant material were screened for the presence of the pinewood nematode (PWN), Bursaphelenchus xylophilus, by sampling wood and bark. Bark beetles were then collected from the gallery systems on the inner side of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…), the beetles were inhabiting the Pinus sp. in Italy, the authors reported the 100% infestation rate since every insect was found infested by nematodes (d'Errico et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), the beetles were inhabiting the Pinus sp. in Italy, the authors reported the 100% infestation rate since every insect was found infested by nematodes (d'Errico et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other species are E. attenuata (Massey 1974) Baujard 1984 E. spondylis Kanzaki, Giblin-Davies andCenter 2009 andE. pini (Massey 1966) Baujard 1984 these were found in the body cavity of Dendroctonus terebrans Olivier, Spondylis buprestoides L. and Ips sexdentatus Boerner respectively (Massey 1974;Kanzaki et al 2009;d'Errico et al 2020). The rest of the Ektaphelenchoides species were not reported in association with insect, these were either isolated from the bark samples having bark beetle galleries or from the rhizosphere of different woody perennials.…”
Section: Introductionmentioning
confidence: 99%